Semantics of Ideological Terms in English, German, Russian and Latvian Lexicography, Textual Use and Translation - Veisbergs, Andrejs (Vertimo studijos, 2024)
Political and ideological terms have been widely used in languages for centuries, their denotational and connotational meaning though fluctuates, reflecting the changing ideological trends. Ideology becomes part of the meaning of these lexemes. It is also compounded into mental structures, which naturally may vary across different ideological groups. Broad uncertainty and ambiguity can be seen in texts: people have varying understandings and ascribe different meanings to political terms on the basis of their experience, political preferences, and the swinging impact of mainstream media. The paper investigates the semantics of the terms liberal and liberalism by analyzing their co-occurrence patterns in corpora of four languages: English, German, Russian, and Latvian. The co-occurrence analysis of corpora reveals that while there are core similarities in the semantics of liberal and liberalism across languages, each language also imbues these terms with unique cultural and historical connotations. This information is contrasted with the dictionary lemmas of the terms which mostly seem to reflect the old meanings. While dictionary definitions provide a baseline understanding, co-occurrence patterns in language use offer deeper insights into how these terms are perceived and interpreted across different societies. This, in its turn, affects the possible translation strategies.